Contextual interference: New findings, insights, and implications for skill acquisition - Wright, D. L.; Kim, T. (Skill acquisition in sport: research, theory and practice, 2020)
Contextual interference: new findings, new insights, and implications for skill acquisition. Understanding how to optimize the organization of practice has long been of central interest to researchers and practitioners alike. It is now common to hear education specialists refer to "best practices" when recognizing teaching environments that are associated with positive learning outcomes. Learning in the movement domain is no different as we seek to identify and use "best practices" that support the acquisition and recovery of perceptual-motor skills, as well as continue to modify and improve these approaches based on a solid understanding as to why they are effective. The following sections review the early and more recent evidence for the claim that teachers, instructors, coaches, and clinicians should strive to incorporate greater contextual interference (CI) into each bout of training or rehabilitation because when this occurs, greater "mental rigor" is demanded, which in turn results in superior long-term retention of practiced skills. In essence, the inclusion of more CI in practice might be considered as an evidenced-based best practice for learning motor skills such as those commonly encountered in sports and domains that place a high premium on motor skill acquisition for success (such as the music industry, the military, and rehabilitation settings).